Criatividade em crianças com dificuldade de aprendizagem: avaliação e intervenção através de procedimentos tradicional e assistido - Dias, Tatiane Lebre (2004)
There are low expectations of creative and cognitive performance in students with learning disability (LD). This situation worsens due to the problems of definition and evaluation from these areas. Aiming at contribution for changes in these expectations and for the study of the relationship between these areas, a contribution of two approaches of cognitive assessment – traditional and assisted was done for the study of creativity in 34 students (8 to 12 years) attending second and third grades in a public school in Vitória, ES with an indication of learning disability (LD) by the low performance in the School Performance Test (SPT). The students were distributed in control and experimental groups (CG and EG), the last being submitted by a development program of creativity (25 sessions over 3 months) approaching the verbal and figurative areas. On the pre-test and posttest, some evaluations were applied: a) traditional – academic (SPT), cognitive (WISC and Raven Progressive Colorful Matrices) and of creativity (Torrance tests of creative thinking); and b) assisted – Constraint – seeking questions of several pictures (C-SQ) having phases with no help, of assistance, maintenance and transfer which look into strategies for the constraint – seeking questions and provide a profile of performance (high score, gainer, non-maintainer, transferrer and non-transferrer). The SPT was reapplied as a follow-up three months after the post-test. Initially, in the traditional assessment the groups did not show any 10 difference in the WISC (average Total-IQ: 92) however in the post-test they had a significant intra-group increase in the Total-IQ (98) and Execution-IQ (95); in Raven the groups initially displayed significant differences favorable to CG (66; EG: 47) which extinguished in the post-test (CG: 68; EG: 60); in Torrance, in the post test, EG increased significantly the means in fluency verbal (pre: 15.4; pos: 21.4) and flexibility verbal (pre: 8.5; post: 11.1), whereas CG increased in flexibility verbal (pre: 7.7; post: 10.1). In the assisted assessment, between the pre and post-test, there was an increase of the high-score profile in both groups, being greater in the EG (from I to 8; GC: from 6 to 10); it also increased the transferrer profile in the EG (from 10 to 16) whereas it kept the same in the CG (16). The significant differences between the groups showed the positive effects for the development program of creativity and the adequacy of these approaches in the evaluation and intervention over the cognitive areas and the creativity of the assessed students.